Security Interaction of Web Services in Heterogeneous Platforms - Tao Xu; Xin Hu; Jiwen Xie; Shujuan Sun (Institute of Advanced Engineering and Science, 2014)
Currently, there are a large number of heterogeneous platforms. The standards of Web Services in different platforms are different and complex. Therefore, security interaction of Web services based on heterogeneous platform has become increasingly prominent. In order to realize security interaction of heterogeneous platforms, a security interactive model of Web Service based on WebSphere and .NET is proposed in this paper. The model adopts an approach based on predicate logic to integrate the security policies of heterogeneous platforms and uses the integrated policy to sign the SOAP message. The experimental results show that the model can ensure the safety of SOAP message transmission and realize the security session between these two heterogeneous platforms. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4734